2022
DOI: 10.4254/wjh.v14.i3.504
|View full text |Cite
|
Sign up to set email alerts
|

New progress in understanding roles of nitric oxide during hepatic ischemia-reperfusion injury

Abstract: Hepatic ischemia-reperfusion injury (HIRI) is a major clinical cause of morbidity and mortality in liver surgery and transplantation. Many studies have found that nitric oxide (NO) plays an important role in the HIRI and its increase or decrease can affect the progression and outcome of HIRI. However, the role of NO in HIRI is controversial and complicated. NO derived by endothelial NO synthase (eNOS) shows a protective role in HIRI, while excessive NO derived by inducible NO synthase (iNOS) accelerates inflam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 62 publications
0
5
0
Order By: Relevance
“…The NO produced by the constitutive form of NO synthase (eNOS) has a protective effect by improving hepatic microcirculation and counteracting the offensive properties of ROS. In contrast, an increased level of NO released following activation of the inducible form of NOS (iNOS) during reperfusion contributes to peroxynitrite formation, leading to lipoperoxidation, endothelial dysfunction, aggravation of proin ammatory response and worsening of the liver injury [39]. Interestingly, our results revealed that TQloaded SNEDDS suppressed iNOS expression, suggesting that TQ-loaded SNEDDS has maintained a physiological amount of NO.…”
Section: Discussionmentioning
confidence: 61%
“…The NO produced by the constitutive form of NO synthase (eNOS) has a protective effect by improving hepatic microcirculation and counteracting the offensive properties of ROS. In contrast, an increased level of NO released following activation of the inducible form of NOS (iNOS) during reperfusion contributes to peroxynitrite formation, leading to lipoperoxidation, endothelial dysfunction, aggravation of proin ammatory response and worsening of the liver injury [39]. Interestingly, our results revealed that TQloaded SNEDDS suppressed iNOS expression, suggesting that TQ-loaded SNEDDS has maintained a physiological amount of NO.…”
Section: Discussionmentioning
confidence: 61%
“…It is well documented that ATP7B is intertwined with lipid metabolism and can damage crucial cellular organelles for ROS energy metabolism during the development of Wilson’s disease ( 31 , 32 ). Excess ROS production can inhibit other antioxidant defense mechanisms in HIRI, leading to increased oxidative damage ( 33 , 34 ). Thus, further exploration of the role of ATP7B in the pathogenesis of HIRI is necessary for future detailed insights.…”
Section: Discussionmentioning
confidence: 99%
“…There is evidence that NO deficiency occurs during ischemia-reperfusion [ 30 ]. It is assumed that early endothelial damage worsens the production of NO, which eliminates the endogenous antineutrophilic effects of NO [ 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%